City Gas Network Uses and Benefits Socialization For Community In Tanjung Gedong Area of West Jakarta - Prayang Sunny Yulia; Arinda Ristawati; Andry Prima; Riskaviana Kurniawati; Aqlyna Fattahanisa; Puri Wijayanti (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
City gas network socialization is a community service that aims to make community understand the development of the city gas distribution sector in Indonesia and provide information to the community about liquified petroleum gas (LPG) substitute. A gas network for households means distributing gas through pipes to households. The limited availability of household gas in DKI Jakarta made this socialization theme raised. The location chosen is the Tanjung Gedong area, Tomang-sub district, Grogol Petamburan district, West Jakarta, which in this case, the area is a densely populated area, especially family settlements. The participants who took part in this community service were housewives. The method used is to provide socialization about the city gas network developed by the government for household gas purposes, the socialization is carried out online with the zoom facility and some others offline in the community while still using the existing health protocol. The result of this community service activity is that the community can recognize and understand the existence of a gas network whose infrastructure development is being developed by the government through PT Perusahaan Gas Negara (PGN) Tbk. This community service makes the community aware of the flow of the city gas network development program.